(untitled) (Journal of Naval Architecture and Marine Engineering, 2022)
This paper presents the result obtained from a series of experiments conducted on different scaled rectangular tanks mounted on shake table, to study the scale effects of sloshing with sway excited motion. Three different tanks of model scales of 1:86, 1:57 and 1:43 are considered for present study. The tests are carried out for the aspect ratio (hs/l, where hs liquid depth and l is the length of the tank) of 0.1625, 0.325, and 0.4875 which represents 25%, 50% and 75% of liquid fill levels, respectively. The sloshing oscillations occur in the longitudinal axis when subjected to sway excitations. Sloshing forces and sloshing oscillation time histories are measured using load cells and wave probes, respectively. The effect of excitation amplitudes and excitation frequencies on sloshing oscillations and sloshing force are presented herein. It is found that violent sloshing is experienced for 50% filled condition irrespective of scaled tanks, excitation amplitudes and excitation frequencies. The sloshing force is maximum in 1:43 scaled tank than other scaled sloshing tanks irrespective of the excitation frequency and amplitude for 50% fill level. Based on the experimental observations and analysis of results, it is concluded that proportionate volume of water and tank size decides the severity of sloshing in the partially filled moving tanks. Journal of Naval Architecture and Marine Engineering Vol 19(2), December, 2022 p. 97-111